Diabetes mellitus associated neurovascular lesions in the retina and brain: A review - Sinclair, Stephen H.; Miller, Elan; Talekar, Kiran S.; Schwartz, Stanley S. (Frontiers in Ophthalmology, 2022)
Diabetes mellitus (DM) is now recognized as a system-wide, autoimmune, inflammatory, microvascular disorder, which, in the retina and brain results in severe multifocal injury now recognized as a leading cause, world-wide, of progressive vision loss and dementia. To address this problem, resulting primarily from variations in glycemia in the prediabetic and overt diabetic states, it must be realized that, although some of the injury processes associated with diabetes may be system wide, there are varying responses, effector, and repair mechanisms that differ from organ to organ or within varying cell structures. Specifically, within the retina, and similarly within the brain cortex, lesions occur of the “neurovascular unit”, comprised of focal microvascular occlusions, inflammatory endothelial and pericyte injury, with small vessel leakage resulting in injury to astrocytes, Müller cells, and microglia, all of which occur with progressive neuronal apoptosis. Such lesions are now recognized to occur before the first microaneurysms are visible to imaging by fundus cameras or before they result in detectable symptoms or signs recognizable to the patient or clinician. Treatments, therefore, which currently are not initiated within the retina until edema develops or progression of vascular lesions that define the current staging of retinopathy, and in the brain only after severe signs of cognitive failure. Treatments, therefore are applied relatively late with some reduction in progressive cellular injury but with resultant minimal vision or cognitive improvement. This review article will summarize the multiple inflammatory and remediation processes currently understood to occur in patients with diabetes as well as pre-diabetes and summarize as well the current limitations of methods for assessing the structural and functional alterations within the retina and brain. The goal is to attempt to define future screening, monitoring, and treatment directions that hopefully will prevent progressive injury as well as enable improved repair and attendant function.